Os atravessamentos do discurso médico na experiência subjetiva de parturição de usuárias do Sistema Único de Saúde: reflexões a partir da psicologia perinatal - Goes, Raissa Melo de (2021)
Until the 17th century, childbirth was not considered a medical act and it was the midwife’s responsibility. Gradually, the figure of the surgeon appears on the scene, the midwife loses her primacy and childbirth becomes an increasingly complex medical procedure. The high rates of maternal and neonatal mortality have redefined childbirth as a potentially risky situation, transforming the hospital environment and the use of sophisticated technology into synonymous with safety. In the same period, medicine sought to strengthen itself as a science, seeking to adapt its practices to the positivism of the time, excluding subjectivity from its field of knowledge. A hegemonic medical discourse emerges in relation to health practices that even today seem to come to normalize and regulate life in modern society. However, understanding that psychoanalysis comes to point out that not everything that affects the body is of the physiological order, we seek through this theory to look at the birth scene, elucidating the subjectivity of the parturient and its influence on the bodily consequences of childbirth. Thus, this dissertation aimed to analyze how the medical discourse reverberates in the subjective experience of women during the process of giving birth. Through birth reports and semi-structured interviews conducted online, we carried out a comprehensive analysis of the process of elaboration of the experience of labor for primiparas in the Unified Health System (SUS), pointing to the existence of psychic work during the labor and we show how this experience, as it occurs in a body inhabited by a subject, is influenced by the medical discourse present in the scene. We elucidate with this the importance of also taking care of the subjective aspects of the parturient during her labor and the need to rethink medical practices since training.